2023
DOI: 10.26434/chemrxiv-2022-77wr7-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specifications Grading at Scale: Improved Letter Grades and Grading-Related Interactions in a Course with over 1,000 Students

Abstract: In our previous work we piloted a specifications grading system in an organic chemistry laboratory course with 37 students. Our current work describes the scale up of that specifications grading system to a course with over 1,000 students. Strategies used for keeping the system manageable and mitigating the time commitment required to do so are described. We found that the time necessary to grade student work and manage the specifications grading implementation of the course was not any greater than for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Studies have shown that introductory STEM courses typically focus on assessing lower-level cognitive skills (typically using multiple choice questions), which have been found to negatively impact students from underrepresented groups (Shah et al, 2022). Grading techniques like mastery-based assessments, standards-based grading, and specifications-based grading systems have been shown to increase student grades and provide more equitable environments for student learning (Boesdorfer et al, 2018;Bowen and Cooper, 2022;Rosa et al, 2022;McKnelly et al, 2023). These findings are significant because research has shown a positive correlations between a student's success in a first-year chemistry course and their likelihood of completing a degree in a STEM-related field (Allenbaugh and Herrera, 2014;Stone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that introductory STEM courses typically focus on assessing lower-level cognitive skills (typically using multiple choice questions), which have been found to negatively impact students from underrepresented groups (Shah et al, 2022). Grading techniques like mastery-based assessments, standards-based grading, and specifications-based grading systems have been shown to increase student grades and provide more equitable environments for student learning (Boesdorfer et al, 2018;Bowen and Cooper, 2022;Rosa et al, 2022;McKnelly et al, 2023). These findings are significant because research has shown a positive correlations between a student's success in a first-year chemistry course and their likelihood of completing a degree in a STEM-related field (Allenbaugh and Herrera, 2014;Stone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%